KEPUTUSAN PEMBELIAN NAAVAGREEN NATURAL SKINCARE DITINJAU DARI STORE ATMOSPHERE , BRAND AMBASSADOR DAN KUALITAS PELAYANAN ( Studi Pada Pelanggan Naavagreen Natural Skincare Cabang Kartasura ) - Eni Lestari; Sarsono Sarsono; Fithri Setya Marwati (ITB AAS Indonesia Surakarta, 2023)
This study aims to determine the effect of store atmosphere, brand ambassadors and service quality on purchasing decisions at the Naavagreen Beauty Clinic, Kartasura Branch. Quantitative approach used in this research. The population in this study is Naavagreen Natural Skincare customers who have purchased products and used treatment services at the Naavagreen Clinic at least 2 times. The population in this study is not known with certainty. The sample in this study was 100 respondents, and the sampling technique used was purposive sampling. With the help of SPSS statistics 25, data analysis in this study included classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear analysis, model feasibility test (F test), t test and coefficient of determination (R2). The results of this study show that partially the store atmosphere, brand ambassador and service quality have a positive and significant effect on purchasing decisions, whereas in the t test brand ambassadors do not have a significant effect on purchasing decisions. Store atmosphere has a positive and significant effect on purchasing decisions, and service quality has a positive and significant effect on purchasing decisions Keywords : Purchase decision, store atmosphere, brand ambassador and service quality